L-Leucine Promotes STAT1 and ISGs Expression in TGEV-Infected IPEC-J2 Cells via mTOR Activation - Du, Jian; Chen, Daiwen; Yu, Bing; He, Jun; Yu, Jie; Mao, Xiangbing; Luo, Yuheng; Zheng, Ping; Luo, Junqiu (Frontiers in Immunology, 2021)
L-leucine (Leu), as one of the effective amino acids to activate the mTOR signaling pathway, can alleviate transmissible gastroenteritis virus (TGEV) infection. However, the underlying mechanism by which Leu alleviates the virus infection has not been fully characterized. In particular, how Leu impacts TGEV replication through mTOR signaling has yet to be elucidated. In the present study, we found that TGEV proliferated efficiently in intestinal porcine epithelial cells (IPEC-J2 cells) as evidenced by the increase in viral contents by flow cytometry, the inhibition of cell proliferation by CCK-8 assay as well as the reduction of PCNA level by western blot. Besides, western blot analysis showed that STAT1 expression was markedly reduced in TGEV-infected cells. The results of ELISA revealed the inhibition of ISGs (ISG56, MxA, and PKR) expressions by TGEV infection. TGEV-induced mTOR and its downstream p70 S6K and 4E-BP1, STAT1 and ISGs downregulation were blocked by an mTOR activator-MHY1485 but not by an mTOR inhibitor-RAPA. Concurrently, mTOR activation by MHY1485 reduced the contents of TGEV and vice versa. Furthermore, Leu reversed the inhibition of STAT1 and ISGs by activating mTOR and its downstream p70 S6K and 4E-BP1 in TEGV-infected cells. Our findings demonstrated that Leu promoted the expressions of STAT1 and ISGs via activating mTOR signaling in IPEC-J2 cells, aiming to prevent TGEV infection.